Comparative and Phylogenetic Analysis Based on the Chloroplast Genome of Coleanthus subtilis (Tratt.) Seidel, a Protected Rare Species of Monotypic Genus - Ren, Jing; Tian, Jing; Jiang, Hui; Zhu, Xin-Xin; Mutie, Fredrick Munyao; Wanga, Vincent Okelo; Ding, Shi-Xiong; Yang, Jia-Xin; Dong, Xiang; Chen, Ling-Ling; Cai, Xiu-Zhen; Hu, Guang-Wan (Frontiers in Plant Science, 2022)
Coleanthus subtilis (Tratt.) Seidel (Poaceae) is an ephemeral grass from the monotypic genus Coleanthus Seidl, which grows on wet muddy areas such as fishponds or reservoirs. As a rare species with strict habitat requirements, it is protected by law at the international and national levels. Despite this, its chloroplast genome and the related relevant information has not been reported to date. In this study, we sequenced its whole chloroplast genome using the Next-generation Sequencing (NGS) technology on the Illumina platform, and performed a comparative and phylogenetic analysis of the related species in Poaceae. The complete chloroplast genome of C. subtilis is 135,915 bp in length and exhibits a typical quadripartite structure, with two 21,529 bp inverted repeat regions (IRs) dividing the entire circular genome into a large single copy region (LSC) of 80,100 bp and a small single copy region (SSC) of 12,757 bp. The overall GC content is 38.3%, while the GC contents in LSC, SSC, and IR regions are 36.3%, 32.4%, and 43.9%, respectively. A total of 129 genes were annotated in chloroplast genome, including 83 protein-coding genes, 38 tRNA genes and 8 rRNA genes. In addition, accD, ycf1, ycf2 and ycf15 genes were found to have been lost. Although the chloroplast genome structure of C. subtilis was found to be conserved and stable in general, 26 SSRs and 13 highly variable loci were detected, these regions have the potential to be developed as important molecular markers. Phylogenetic analysis with species in the family Poaceae showed that Coleanthus and Phippsia were sister groups, which was in agreement with the previous studies. Furthermore, new insights into the relationship between Coleanthus, Zingeria and Colpodium were also provided. This study is important because apart from being the initial chloroplast genome report of C. subtilis, it also provides important genomic information for its conservation and enrichment of data for further research on its origin.